The Role of Conflict Management in Resolving Conflicts in Organizations - Ariani, Fadillah (Pascasarjana Universitas Pasundan, 2024)
Conflict is a phenomenon that cannot be avoided in human life, including in the context of office administration. Conflict can occur due to various factors, such as differences in interests, goals, values, or communication styles. If not managed well, conflict can have a negative impact on the organization, such as reduced productivity, increased stress, and damaged interpersonal relationships. Therefore, it is important for organizations to have an effective conflict management strategy. Effective conflict management can increase collaboration, innovation and job satisfaction, as well as prevent conflict escalation that is detrimental to the organization, and can help organizations to manage conflict productively and not cause negative impacts. Conflict is not always detrimental but can also be beneficial in the long term. Meanwhile, according to the interactionist view, conflict is something that must be stimulated, because conflict can encourage change in the organization. There is not a single organization/company that has never experienced conflict, both internal and external, conflict will only disappear along with the disappearance of society itself. The author presents this article in order to contribute ideas regarding conflict resolution in order to change behavior and make the parties in conflict aware of their mistakes. Awareness of mistakes is able to increase productivity, and is not detrimental but instead brings wisdom and benefits to the organization/company concerned.